Contribution of magnetic nuclear resonance to the diagnosis of Creutzfeldt-Jakob disease - Albuquerque, Leonardo Cordenonzi Pedroso de; Duarte, Juliana Avila; Schuh, Artur Francisco Schumacher (Clinical and Biomedical Research, 2015)
A 71 year-old woman presented to our hospital with acute onset of progressive cognitive impairment and psychotic symptoms. Five weeks earlier, she noticed memory impairment and diplopia. After two weeks, she was admitted to a psychiatric hospital due to delusions, agitation and hallucinations. After three weeks, she was referred to our hospital with progressive deterioration, especially impairment of language and gait. At admission, examination showed aphasia, myoclonic jerks, apraxic gait and Babinski’s sign. Laboratory tests showed mild elevation in anti-TPO titer. Other laboratory studies were normal. EEG showed a semi-periodic pattern of widespread sharp-wave discharges with periods of an arrhythmic widespread theta waves. Brain magnetic resonance imaging (MRI) showed hyperintensity on FLAIR and decreased diffusivity in the basal ganglia, specially in the head of caudate and putamen, as well as in the cortex of frontal lobes bilaterally, left parietal lobe and bilateral occipital lobes on diffusion weighted images (DWI) and apparent diffusion map (ADC). There was no gadolinium enhancement. Diagnosis of probable Creutzfeldt-Jakob disease was made.